PARADIGMA NAHDLATUL ‘ULAMA TERHADAP MODERNISASI - Sunarto AS, A. (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2013)
Islam in Indonesia has been running quite unique, from the beginning of Islam so easy and quick to respond, ollowed by the public until after the battle of thought put Islam in the public sphere. So many conceptual contribution is expected to respond to the needs of people from vfarious Islamic thinkers, even by young Muslims. And in this paper, the authors also conducted an in-depth study to search the Islamic identity that can be felt responsive and grounded in the soil of Indonesia. Studies done by dissecting the religious rules,